Skip to main content

A note on degenerate r-Stirling numbers

Abstract

The aim of this paper is to study the unsigned degenerate r-Stirling numbers of the first kind as degenerate versions of the r-Stirling numbers of the first kind and the degenerate r-Stirling numbers of the second kind as those of the r-Stirling numbers of the second kind. For the degenerate r-Stirling numbers of both kinds, we derive recurrence relations, generating functions, explicit expressions, and some identities involving them.

Introduction

Let \([n]=\{1,2,3,\ldots ,n\}\). The unsigned Stirling number of the first kind \({n \brack k}\) is the number of permutations of the set \([n]\) with exactly k disjoint cycles, while the Stirling number of the second kind \({n \brace k}\) counts the number of partitions of the set \([n]\) into k nonempty disjoint subsets. Let r be a positive integer. The unsigned r-Stirling number of the first kind \({n \brack k}_{r}\) is the number of permutations of the set \([n]\) with exactly k disjoint cycles in such a way that the numbers \(1,2,\ldots ,r\) are in distinct cycles, while the r-Stirling number of the second kind \({n \brace k}_{r}\) counts the number of partitions of the set \([n]\) into k nonempty disjoint subsets in such a way that the numbers \(1,2,\ldots ,r\) are in distinct subsets. We remark that Border [1] studied the combinatorial and algebraic properties of the r-Stirling numbers.

Carlitz initiated a study of the degenerate Bernoulli and Euler polynomials and numbers. In recent years, some mathematicians have explored various degenerate versions of many special polynomials and numbers by employing various tools like combinatorial methods, generating functions, differential equations, umbral calculus techniques, p-adic analysis, and probability theory. These degenerate versions include the degenerate Stirling numbers of the first and second kinds, degenerate Bernoulli numbers of the second kind, and degenerate Bell numbers and polynomials of which interesting arithmetical and combinatorial results were obtained (see [7, 911, 13] and references therein). Especially, it turns out that the degenerate Stirling numbers of the first and second kind (see (17), (18)) appear very frequently when we study degenerate versions of some special numbers and polynomials [7, 9, 13, 16].

The aim of this paper is to study the unsigned degenerate r-Stirling numbers of the first kind \({n \brack k}_{r,\lambda }\) as degenerate versions of the r-Stirling numbers of the first kind \({n \brack k}_{r}\) and the degenerate r-Stirling numbers of the second kind \({n \brace k}_{r,\lambda }\) as degenerate versions of the r-Stirling numbers of the second kind \({n \brace k}_{r}\). They can be viewed also as natural extensions of the degenerate Stirling numbers of the first kind \({n \brack k}_{\lambda }\) and the degenerate Stirling numbers of the second kind \({n \brace k}_{\lambda }\) which were introduced earlier [79, 12]. For the degenerate r-Stirling numbers of both kinds, we derive recurrence relations, generating functions, explicit expressions, and some identities involving them.

The outline of this paper is as follows. In Sect. 1, we recall the degenerate exponential functions, the rising and falling λ-factorial sequences, recurrence relations and generating functions of r-Stirling numbers, Lah numbers, the degenerate Stirling numbers and the degenerate logarithm functions. In Sect. 2, we introduce the unsigned degenerate r-Stirling numbers of the first kind and the degenerate r-Stirling numbers of the second kind and derive recurrence relations, generating functions, expressions of degenerate r-Stirling numbers in terms of degenerate Stirling numbers, and a representation of the degenerate r-Bell polynomials in terms of the degenerate r-Stirling numbers of the second kind.

For any \(0 \ne \lambda \in \mathbb{R}\), the degenerate exponential functions are defined by

$$ e_{\lambda }^{x}(t)=(1+\lambda t)^{\frac{x}{\lambda }}=\sum _{n=0}^{ \infty }(x)_{n,\lambda } \frac{t^{n}}{n!}\quad (\text{see [7, 10, 11]}), $$
(1)

where the falling λ-factorial sequence is given by

$$ (x)_{0,\lambda }=1,\qquad (x)_{n,\lambda }=x(x-\lambda ) (x-2\lambda )\cdots \bigl(x-(n-1) \lambda \bigr)\quad (n\ge 1). $$
(2)

When \(x=1\), we have

$$ e_{\lambda }(t)=e_{\lambda }^{1}(t)=\sum _{n=0}^{\infty }(1)_{n,\lambda } \frac{t^{n}}{n!}. $$

The rising λ-factorial sequence is defined by

$$ \langle x\rangle _{0,\lambda }=1,\qquad \langle x\rangle _{n,\lambda }=x(x+ \lambda )\cdots \bigl(x+(n-1)\lambda \bigr)\quad (n\ge 1). $$
(3)

When \(\lambda =1\), we have

$$\begin{aligned}& (x)_{0}=1,\qquad (x)_{n}=x(x-1)\cdots (x-n+1)\quad (n\ge 1), \end{aligned}$$
(4)
$$\begin{aligned}& \langle x\rangle _{0}=1,\qquad \langle x\rangle _{n}=x(x+1) \cdots (x+n-1)\quad (n\ge 1). \end{aligned}$$
(5)

Throughout this paper, we assume that r is any positive integer.

It is known that the r-Stirling numbers satisfy the following recurrence relations:

$$\begin{aligned} &{n \brack m}_{r} = (n-1){n-1 \brack m}_{r}+{n-1 \brack m-1}_{r}\quad (n>r), \end{aligned}$$
(6)
$$\begin{aligned} &{n \brace m}_{r} = m{n-1 \brace m}_{r}+ {n-1 \brace m-1}_{r}\quad (n>r), \end{aligned}$$
(7)
$$\begin{aligned} &{n \brack m}_{r}=0,\qquad {n \brace m}_{r}=0, \quad \text{if } n< r, \end{aligned}$$
(8)
$$\begin{aligned} &{n \brack m}_{r}=\delta _{mr}, \qquad {n \brace m}_{r}=\delta _{mr},\quad \text{if } n=r\ (\text{see [1--5, 14]}). \end{aligned}$$
(9)

The r-Stirling numbers of the first kind have the “horizontal” generating function:

$$ \sum_{k=r}^{n} {n \brack k}_{r}z^{k} = z^{r}(z+r)\cdots (z+n-1) = z^{r}\langle z+r\rangle _{n-r}, $$
(10)

where \(n \ge r\) (see [17, 911, 13, 15]).

Thus, by (10), we get

$$ \langle z+r\rangle _{n} = \sum_{k=0}^{n} {n+r \brack k+r}_{r}z^{k}\quad (n\ge 0). $$
(11)

The r-Stirling numbers of the second kind have the “vertical” generating function:

$$ \sum_{n=m}^{\infty }{n \brace m}_{r} z^{n}= \frac{z^{m}}{(1-rz)(1-(r+1)z)\cdots (1-mz)}\quad (m\ge r ), $$
(12)

which is equivalent to

$$ {n+r \brace m+r}_{r}=\frac{1}{m!}\sum _{k=0}^{m}\binom{m}{k}(-1)^{m-k}(r+k)^{n}\quad (n \ge m\ge 0), $$
(13)

and is also equivalent to

$$ \sum_{n=m}^{\infty } {n+r \brace m+r}_{r}\frac{t^{n}}{n!}= \frac{1}{m!} \bigl(e^{t}-1\bigr)^{m} e^{rt}. $$
(14)

From (14), we note that

$$ (z+r)^{n}=\sum_{k=0}^{n} {n+r \brace k+r}(z)_{k}\quad (n\ge 0). $$
(15)

As is well known, the Lah numbers are defined by

$$ L(n,k) = \binom{n-1}{k-1}\frac{n!}{k!}\quad (n\ge k\ge 0). $$
(16)

From (16), we note that

$$ \frac{1}{k!} \biggl(\frac{t}{1-t} \biggr)^{k} = \sum_{n=k}^{\infty }L(n,k) \frac{t^{n}}{n!}\quad (k \ge 0)\ (\text{see [2, 4, 5]}). $$

Recently, the degenerate Stirling numbers of the first kind were defined by

$$ (x)_{n}=\sum_{k=0}^{n}S_{1,\lambda }(n,k) (x)_{k,\lambda }\quad (n\ge 0)\ (\text{see [1--7, 9--11, 13, 15]}), $$
(17)

and the degenerate Stirling numbers of the second kind were defined by

$$ (x)_{n,\lambda }=\sum_{k=0}^{n} {n \brace k}_{\lambda }(x)_{k}\quad (n \ge 0)\ (\text{see [7, 9]}). $$
(18)

Note that

$$ \lim_{\lambda \rightarrow 0}{n \brace k}_{\lambda }= {n \brace k}\quad (n\ge k\ge 0). $$

Let us define the degenerate “unsigned” Stirling numbers of the first kind by

$$ {n \brack k}_{\lambda }=(-1)^{n-k}S_{1,\lambda }(n,k)\quad (n\ge k\ge 0). $$
(19)

Then, replacing x by −x in (17), we get

$$ \langle x\rangle _{n} = \sum_{k=0}^{n} {n \brack k}_{\lambda } \langle x\rangle _{k,\lambda }\quad (n\ge 0). $$
(20)

Note that

$$ \lim_{\lambda \rightarrow 0}{n \brack k}_{\lambda }= {n \brack k}. $$

Let \(\log _{\lambda }t\) be the compositional inverse of \(e_{\lambda }(t)\), called the degenerate logarithm function. Then we have

$$ \log _{\lambda }(1+t)=\sum_{n=1}^{\infty } \lambda ^{n-1}(1)_{n, \frac{1}{\lambda }}\frac{t^{n}}{n!}= \frac{1}{\lambda } \bigl((1+t)^{ \lambda }-1 \bigr) \quad (\text{see [7]}). $$

Note that

$$ e_{\lambda } \bigl(\log _{\lambda }(1+t) \bigr)=\log _{\lambda } \bigl(e_{ \lambda }(1+t) \bigr)=1+t. $$
(21)

Degenerate r-Stirling numbers

In view of (11) and (17), we define the unsigned degenerate r-Stirling numbers of the first kind by

$$ \langle x+r\rangle _{n}=\sum_{k=0}^{n} {n+r \brack k+r}_{r,\lambda } \langle x\rangle _{k,\lambda }\quad (n \ge 0). $$
(22)

Note from (11) and (22) that

$$ \lim_{\lambda \rightarrow 0} {n+r \brack k+r}_{r,\lambda }= {n+r \brack k+r}_{r}. $$

By (22), we get

$$\begin{aligned} \sum_{k=0}^{n+1}{n+1+r \brack k+r}_{r,\lambda }\langle x\rangle _{k, \lambda } &= \langle x+r\rangle _{n+1} \\ & = \langle x+r\rangle _{n}(x+r+n) \\ & = \sum_{k=0}^{n}{n+r \brack k+r}_{r,\lambda }\langle x \rangle _{k,\lambda }(x+k\lambda +r+n-k\lambda ) \\ & = \sum_{k=0}^{n}{n+r \brack k+r}_{r,\lambda }\langle x \rangle _{k+1,\lambda }+ \sum _{k=0}^{n}(n+r-k\lambda ){n+r \brack k+r}_{r, \lambda }\langle x\rangle _{k,\lambda } \\ & = \sum_{k=0}^{n+1}{n+r \brack k-1+r}_{r,\lambda }\langle x \rangle _{k,\lambda }+ \sum _{k=0}^{n}(n+r-k\lambda ){n+r \brack k+r}_{r, \lambda }\langle x\rangle _{k,\lambda } \\ & = \sum_{k=0}^{n+1} \left({n+r \brack k-1+r}_{r,\lambda }+ (n+r-k \lambda ){n+r \brack k+r}_{r,\lambda } \right) \langle x\rangle _{k, \lambda }, \end{aligned}$$
(23)

as

$$ {n+r \brack r-1}_{r,\lambda }=0 \quad \text{and}\quad {n+r \brack n+1+r}_{r, \lambda }=0. $$

Therefore, we obtain the following theorem.

Theorem 2.1

Let n, k be nonnegative integers. Then we have

$$ {n+1+r \brack k+r}_{r,\lambda }= {n+r \brack k-1+r}_{r,\lambda }+ (n+r-k \lambda ){n+r \brack k+r}_{r,\lambda }\quad (n \ge k). $$

In particular,

$$ {n \brack k}_{r,\lambda }= {n-1 \brack k-1}_{r,\lambda }+ \bigl(n-1-(k-r) \lambda \bigr){n-1 \brack k}_{r,\lambda }\quad (n>r, n>k). $$

From (22), we note that

$$\begin{aligned} \biggl(\frac{1}{1-t} \biggr)^{x} \biggl( \frac{1}{1-t} \biggr)^{r} &= \sum _{n=0}^{ \infty }\langle x+r\rangle _{n} \frac{t^{n}}{n!} \\ &= \sum_{n=0}^{\infty }\sum _{k=0}^{n}{n+r \brack k+r}_{r,\lambda } \langle x\rangle _{k,\lambda }\frac{t^{n}}{n!} \\ &= \sum_{k=0}^{\infty } \Biggl(\sum _{n=k}^{\infty }{n+r \brack k+r}_{r, \lambda } \frac{t^{n}}{n!} \Biggr)\langle x\rangle _{k,\lambda }. \end{aligned}$$
(24)

On the other hand, by (21), we get

$$\begin{aligned} \biggl(\frac{1}{1-t} \biggr)^{x} \biggl( \frac{1}{1-t} \biggr)^{r} &= e_{ \lambda }^{-x} \bigl(\log _{\lambda }(1-t) \bigr) \biggl(\frac{1}{1-t} \biggr)^{r} \\ &= \sum_{k=0}^{\infty }\frac{1}{k!} \bigl(-\log _{\lambda }(1-t) \bigr)^{k} \biggl( \frac{1}{1-t} \biggr)^{r}\langle x\rangle _{k,\lambda }. \end{aligned}$$
(25)

Therefore, by (24) and (25), we obtain the following theorem.

Theorem 2.2

For any integer \(k\ge 0\), we have

$$ \frac{1}{k!} \bigl(-\log _{\lambda }(1-t) \bigr)^{k} \biggl(\frac{1}{1-t} \biggr)^{r} = \sum _{n=k}^{\infty }{n+r \brack k+r}_{r,\lambda } \frac{t^{n}}{n!}. $$

From (19) and (20), we have

$$ \frac{1}{k!} \bigl(-\log _{\lambda }(1-t) \bigr)^{k} = \sum_{n=k}^{ \infty }{n \brack k}_{\lambda }\frac{t^{n}}{n!}. $$
(26)

Thus, we get

$$\begin{aligned} \frac{1}{k!} \bigl(-\log _{\lambda }(1-t) \bigr)^{k} \biggl(\frac{1}{1-t} \biggr)^{r} &= \Biggl(\sum _{m=k}^{\infty }{m \brack k}_{\lambda } \frac{t^{m}}{m!} \Biggr) \Biggl(\sum_{l=0}^{\infty } \langle r\rangle _{l} \frac{t^{l}}{l!} \Biggr) \\ &= \sum_{n=k}^{\infty } \Biggl(\sum _{m=k}^{n}\binom{n}{m}{m \brack k}_{ \lambda }\langle r\rangle _{n-m} \Biggr) \frac{t^{n}}{n!}. \end{aligned}$$
(27)

Therefore, by Theorem 2.2 and (27), we obtain the following theorem.

Theorem 2.3

For any nonnegative integers n, k, with \(n \ge k\), we have

$$ {n+r \brack k+r}_{r,\lambda } = \sum_{m=k}^{n} \binom{n}{m}{m \brack k}_{\lambda }\langle r\rangle _{n-m}. $$

Now, we observe that

$$\begin{aligned} \biggl(\frac{1}{1-t} \biggr)^{r} &= \biggl(1+ \frac{t}{1-t} \biggr)^{r} = \sum_{l=0}^{r} \binom{r}{l} \biggl(\frac{t}{1-t} \biggr)^{l} = \sum _{l=0}^{r}(r)_{l} \frac{1}{l!} \biggl(\frac{t}{1-t} \biggr)^{l} \\ &= \sum_{l=0}^{r}(r)_{l} \sum_{j=l}^{\infty }L(j,l)\frac{t^{j}}{j!} = \sum_{j=0}^{\infty } \Biggl(\sum _{l=0}^{\min \{r,j\}}L(j,l) (r)_{l} \Biggr) \frac{t^{j}}{j!}. \end{aligned}$$
(28)

By (28), we get

$$\begin{aligned} &\frac{1}{k!} \bigl(-\log _{\lambda }(1-t) \bigr)^{k} \biggl(\frac{1}{1-t} \biggr)^{r} \\ &\quad = \sum_{m=k}^{\infty }{m \brack k}_{\lambda }\frac{t^{m}}{m!} \sum_{j=0}^{\infty } \Biggl(\sum_{l=0}^{\min \{r,j\}}L(j,l) (r)_{l} \Biggr)\frac{t^{j}}{j!} \\ &\quad = \sum_{n=k}^{\infty } \Biggl\{ \sum _{j=0}^{n-k}\sum _{l=0}^{ \min \{r,j\}}L(j,l) (r)_{l} \binom{n}{j}{n-j \brack k}_{\lambda } \Biggr\} \frac{t^{n}}{n!}. \end{aligned}$$
(29)

Therefore, by Theorem 2.2 and (29), we obtain the following theorem.

Theorem 2.4

For any nonnegative integers n, k, with \(n \ge k\), we have

$$ {n+r \brack k+r}_{r,\lambda }=\sum_{j=0}^{n-k} \sum_{l=0}^{\min \{r,j \}}L(j,l) (r)_{l}\binom{n}{j}{n-j \brack k}_{\lambda }. $$

By (21), we get

$$\begin{aligned} \biggl(\frac{1}{1-t} \biggr)^{r+k} &= e_{\lambda }^{-r-k} \bigl(\log _{ \lambda }(1-t) \bigr) \\ &= \sum_{l=0}^{\infty }\langle r+k\rangle _{l,\lambda }\sum_{n=l}^{ \infty }{n \brack l}_{\lambda }\frac{t^{n}}{n!} \\ &= \sum_{n=0}^{\infty } \Biggl(\sum _{l=0}^{n}\langle r+k\rangle _{l, \lambda }{n \brack l}_{\lambda } \Biggr)\frac{t^{n}}{n!}. \end{aligned}$$
(30)

It is not difficult to show that

$$ \biggl(\frac{1}{1-t} \biggr)^{r+k} = \sum _{n=0}^{\infty } \Biggl(\sum _{l=0}^{n}{n+r \brack l+r}_{r,\lambda }\langle k\rangle _{l,\lambda } \Biggr) \frac{t^{n}}{n!}. $$
(31)

Therefore, by (28), (30), and (31), we obtain the following theorem.

Theorem 2.5

For any nonnegative integers n, k, we have

$$ \sum_{l=0}^{\min \{r+k,n\}}(r+k)_{l}L(n,l)= \sum_{l=0}^{n}\langle r+k \rangle _{l,\lambda }{n\brack l}_{\lambda }=\sum_{l=0}^{n}{n+r \brack l+r}_{r, \lambda }\langle k\rangle _{l,\lambda }. $$

As an inversion formula of (22), we consider the degenerate r-Stirling numbers of second kind given by

$$ (x+r)_{n,\lambda } = \sum_{k=0}^{n}{n+r \brace k+r}_{r,\lambda }(x)_{k}, $$
(32)

where \(n \ge 0\) and \(r\in \mathbb{N}\).

Note from (15) and (32) that

$$ \lim_{\lambda \rightarrow 0}{n+r \brace k+r}_{r,\lambda }={n+r \brace k+r}. $$

From (32), we have

$$\begin{aligned} (x+r)_{n+1,\lambda } &= (x+r)_{n,\lambda }(x+r-n\lambda ) \\ &= \sum_{k=0}^{n}{n+r \brace k+r}_{r,\lambda }(x)_{k}(x-k+k+r-n \lambda ) \\ &= \sum_{k=0}^{n}{n+r \brace k+r}_{r,\lambda }(x)_{k+1}+ \sum_{k=0}^{n}{n+r \brace k+r}_{r,\lambda }(k+r-n\lambda ) (x)_{k} \\ &= \sum_{k=0}^{n+1}{n+r \brace k-1+r}_{r,\lambda }(x)_{k}+ \sum_{k=0}^{n}{n+r \brace k+r}_{r,\lambda }(k+r-n\lambda ) (x)_{k} \\ &= \sum_{k=0}^{n+1} \left({n+r \brace k-1+r}_{r,\lambda }+ (k+r-n \lambda ) {n+r \brace k+r}_{r,\lambda } \right) (x)_{k}, \end{aligned}$$
(33)

since

$$ {n+r \brace r-1}_{r,\lambda }=0\quad \text{and}\quad {n+r \brace n+1+r}_{r, \lambda }=0. $$

Therefore, by (32) and (33), we obtain the following theorem.

Theorem 2.6

For any nonnegative integers n, k, with \(n\ge k\), we have

$$ {n+1+r \brace k+r}_{r,\lambda } = {n+r \brace k-1+r}_{r,\lambda }+ (k+r-n \lambda ) {n+r \brace k+r}_{r,\lambda }. $$

In particular,

$$ {n \brace k}_{r,\lambda } = {n-1 \brace k-1}_{r,\lambda }+ \bigl(k-(n-1-r) \lambda \bigr){n-1 \brace k}_{r,\lambda }, $$

where \(n>r\).

By (32), we get

$$\begin{aligned} e_{\lambda }^{x+r}(t) &= \sum_{n=0}^{\infty }(x+r)_{n,\lambda } \frac{t^{n}}{n!} = \sum_{n=0}^{\infty } \Biggl(\sum_{k=0}^{n}{n+r \brace k+r}_{r,\lambda }(x)_{k} \Biggr)\frac{t^{n}}{n!} \\ &= \sum_{k=0}^{\infty } \Biggl(\sum _{n=k}^{\infty }{n+r \brace k+r}_{r, \lambda } \frac{t^{n}}{n!} \Biggr) (x)_{k}. \end{aligned}$$
(34)

On the other hand,

$$ e^{x+r}_{\lambda }(t) = \bigl(e_{\lambda }(t)-1+1 \bigr)^{x}e_{\lambda }^{r}(t) = \sum _{k=0}^{\infty } \biggl(\frac{1}{k!} \bigl(e_{\lambda }(t)-1 \bigr)^{k}e_{ \lambda }^{r}(t) \biggr) (x)_{k}. $$
(35)

Therefore, by (34) and (35), we obtain the following theorem.

Theorem 2.7

For any nonnegative integer k, we have

$$ \frac{1}{k!} \bigl(e_{\lambda }(t)-1 \bigr)^{k}e_{\lambda }^{r}(t) = \sum_{n=k}^{\infty }{n+r \brace k+r}_{r,\lambda }\frac{t^{n}}{n!}. $$

Now, we observe that

$$\begin{aligned} \frac{1}{k!} \bigl(e_{\lambda }(t)-1 \bigr)^{k}e_{\lambda }^{r}(t) &= \frac{1}{k!}\sum_{j=0}^{k} \binom{k}{j}(-1)^{k-j}e_{\lambda }^{j+r}(t) \\ &= \frac{1}{k!}\sum_{j=0}^{k} \binom{k}{j}(-1)^{k-j}\sum_{n=0}^{ \infty }(j+r)_{n,\lambda } \frac{t^{n}}{n!} \\ &= \sum_{n=0}^{\infty } \Biggl\{ \frac{1}{k!}\sum_{j=0}^{k} \binom{k}{j}(-1)^{k-j}(j+r)_{n,\lambda } \Biggr\} \frac{t^{n}}{n!}. \end{aligned}$$
(36)

Therefore, by Theorem 2.7 and (36), we obtain the following theorem.

Theorem 2.8

For any nonnegative integers n, k, we have

$$ \frac{1}{k!}\sum_{j=0}^{k} \binom{k}{j}(-1)^{k-j}(j+r)_{n,\lambda } = \textstyle\begin{cases} {n+r \brace k+r}_{r,\lambda }, & \textit{if }n\ge k, \\ 0, & \textit{otherwise}. \end{cases} $$

In particular,

$$ \frac{1}{(k-r)!}\sum_{j=0}^{k-r} \binom{k-r}{j}(-1)^{k-r-j}(j+r)_{n-r, \lambda } = {n \brace k}_{r,\lambda } \quad (n\ge k \ge r). $$

The double generating function is given by

$$\begin{aligned} e_{\lambda } \bigl(t\bigl(e_{\lambda }(x)-1\bigr) \bigr)e_{\lambda }^{r}(x) &= \sum_{m=0}^{ \infty }t^{m}(1)_{m,\lambda } \frac{1}{m!} \bigl(e_{\lambda }(x)-1 \bigr)^{m}e_{ \lambda }^{r}(x) \\ &= \sum_{m=0}^{\infty }t^{m}(1)_{m,\lambda } \sum_{k=m}^{\infty }{k+r \brace m+r}_{r,\lambda }\frac{x^{k}}{k!} \\ &= \sum_{k=0}^{\infty } \Biggl(\sum _{m=0}^{k}t^{m}(1)_{m,\lambda }{k+r \brace m+r}_{r,\lambda } \Biggr)\frac{x^{k}}{k!}. \end{aligned}$$
(37)

Let us define the degenerate r-Bell polynomials as follows:

$$ e_{\lambda } \bigl(t\bigl(e_{\lambda }(x)-1\bigr) \bigr)e_{\lambda }^{r}(x) = \sum_{n=0}^{ \infty } \mathrm{Bel}_{n,\lambda }^{(r)}(t)\frac{x^{n}}{n!}. $$
(38)

From (37) and (38), we have

$$ \mathrm{Bel}_{n,\lambda }^{(r)}(t) = \sum _{m=0}^{n}t^{m}(1)_{m, \lambda }{n+r \brace m+r}_{r,\lambda }\quad (n\ge 0). $$

Theorem 2.9

For any nonnegative integer n, we have

$$ \mathrm{Bel}_{n,\lambda }^{(r)}(t) = \sum _{m=0}^{n}{n+r \brace m+r}_{r, \lambda }(1)_{m,\lambda }t^{m}. $$

By Theorem 2.7, we get

$$\begin{aligned} \frac{1}{k!} \bigl(e_{\lambda }(t)-1 \bigr)^{k}e_{\lambda }^{r}(t) &= \frac{1}{k!} \bigl(e_{\lambda }(t)-1 \bigr)^{k} \bigl(e_{\lambda }(t)-1+1 \bigr)^{r} \\ &= \sum_{j=0}^{r}\binom{r}{j} \frac{1}{k!} \bigl(e_{\lambda }(t)-1 \bigr)^{k+j} \\ &= \sum_{j=0}^{r}(r)_{j} \binom{k+j}{k}\sum_{n=j+k}^{\infty }{n \brace j+k}_{\lambda }\frac{t^{n}}{n!} \\ &= \sum_{n=k}^{\infty } \Biggl\{ \sum _{j=0}^{\min \{r,n-k\}}(r)_{j} \binom{k+j}{k}{n \brace j+k}_{\lambda } \Biggr\} \frac{t^{n}}{n!}. \end{aligned}$$
(39)

From (39), we have

$$ {n+r \brace k+r}_{r,\lambda } = \sum_{j=0}^{\min \{r,n-k\}}(r)_{j} \binom{k+j}{k}{n \brace j+k}_{\lambda }. $$
(40)

Therefore, by (40), we obtain the following theorem.

Theorem 2.10

For any nonnegative integers n, k, with \(n\ge k\), we have

$$ {n+r \brace k+r}_{r,\lambda } = \sum_{j=0}^{\min \{r,n-k\}}(r)_{j} \binom{k+j}{k}{n \brace j+k}_{\lambda }. $$

Now, we observe that

$$\begin{aligned} \frac{1}{k!} \bigl(-\log _{\lambda }(1-t) \bigr)^{k} \biggl(\frac{1}{1-t} \biggr)^{r} &= \frac{1}{k!} \bigl(-\log _{\lambda }(1-t) \bigr)^{k}e_{ \lambda }^{-r} \bigl(\log _{\lambda }(1-t) \bigr) \\ & = \frac{1}{k!} \bigl(-\log _{\lambda }(1-t) \bigr)^{k}\sum_{l=0}^{ \infty } \langle r\rangle _{l,\lambda }\frac{1}{l!} \bigl(-\log _{\lambda }(1-t) \bigr)^{l} \\ & = \sum_{l=0}^{\infty }\frac{(k+l)!}{k!l!} \langle r\rangle _{l, \lambda }\frac{1}{(k+l)!} \bigl(-\log _{\lambda }(1-t) \bigr)^{k+l} \\ & = \sum_{l=0}^{\infty }\binom{k+l}{l} \langle r\rangle _{l,\lambda } \sum_{n=k+l}^{\infty }{n \brack k+l}_{\lambda }\frac{t^{n}}{n!} \\ & = \sum_{n=k}^{\infty } \Biggl(\sum _{l=0}^{n-k}\binom{k+l}{l} \langle r\rangle _{l,\lambda }{n \brack k+l}_{\lambda } \Biggr) \frac{t^{n}}{n!}. \end{aligned}$$
(41)

By Theorem 2.2 and (41), we get

$$ {n+r \brack k+r}_{r,\lambda } = \sum_{l=0}^{n-k} \binom{k+l}{l}{n \brack k+l}_{\lambda }\langle r\rangle _{l,\lambda }, $$
(42)

where n, k are nonnegative integers, with \(n\ge k\).

Therefore, by (42), we obtain the following theorem.

Theorem 2.11

For any nonnegative integers n, k, with \(n\ge k\), we have

$$ {n+r \brack k+r}_{r,\lambda } = \sum_{l=0}^{n-k} \binom{k+l}{l}{n \brack k+l}_{\lambda }\langle r\rangle _{l,\lambda }. $$

Conclusion

In this paper, we studied the unsigned degenerate r-Stirling numbers of the first kind \({n \brack k}_{r,\lambda }\) as degenerate versions of the r-Stirling numbers of the first kind \({n \brack k}_{r}\) and the degenerate r-Stirling numbers of the second kind \({n \brace k}_{r,\lambda }\) as degenerate versions of the r-Stirling numbers of the second kind \({n \brace k}_{r}\). They can be viewed also as natural extensions of the degenerate Stirling numbers of the first kind \({n \brack k}_{\lambda }\) and the degenerate Stirling numbers of the second kind \({n \brace k}_{\lambda }\), which were introduced earlier. For the degenerate r-Stirling numbers of both kinds, we derived recurrence relations, generating functions, expressions of degenerate r-Stirling numbers in terms of degenerate Stirling numbers, and a representation of the degenerate r-Bell polynomials in terms of the degenerate r-Stirling numbers of the second kind.

As it turns out, the degenerate Stirling numbers appear very frequently when we study degenerate versions of many special numbers and polynomials [7, 9, 13]. It would be very interesting to discover many appearances of the degenerate r-Stirling numbers in such studies. It is one of our future projects to continue to explore degenerate versions of some special numbers and polynomials and their applications not only in mathematics but also in other disciplines like statistics, physics, engineering, and social sciences.

References

  1. 1.

    Broder, A.: The r-Stirling numbers. Discrete Math. 49(3), 241–259 (1984)

    MathSciNet  Article  Google Scholar 

  2. 2.

    Carlitz, L.: Weighted Stirling numbers of the first and second kind. I. Fibonacci Q. 18(2), 147–162 (1980)

    MathSciNet  MATH  Google Scholar 

  3. 3.

    Carlitz, L.: Weighted Stirling numbers of the first and second kind. II. Fibonacci Q. 18(3), 242–257 (1980)

    MathSciNet  MATH  Google Scholar 

  4. 4.

    Comtet, L.: Analyse combinatoire, Tomes I, II (French) Collection SUP: “Le Mathématicien”, 4, 5. Presses Universitaires de France, Paris (1970)

  5. 5.

    Comtet, L.: Advanced Combinatorics: The Art of Finite and Infinite Expansions, Revised and enlarged edn. Reidel, Dordrecht (1974)

    Google Scholar 

  6. 6.

    Kim, D.S., Kim, T.: A note on polyexponential and unipoly functions. Russ. J. Math. Phys. 26(1), 40–49 (2019)

    MathSciNet  Article  Google Scholar 

  7. 7.

    Kim, D.S., Kim, T.: A note on a new type of degenerate Bernoulli numbers. Russ. J. Math. Phys. 27(2), 227–235 (2020)

    MathSciNet  Article  Google Scholar 

  8. 8.

    Kim, D.S., Kim, T.: Degenerate Sheffer sequences and λ-Sheffer sequences. J. Math. Anal. Appl., 124521 (2020). https://www.sciencedirect.com/science/article/pii/S0022247X20306831

  9. 9.

    Kim, T.: A note on degenerate Stirling polynomials of the second kind. Proc. Jangjeon Math. Soc. 20(3), 319–331 (2017)

    MathSciNet  MATH  Google Scholar 

  10. 10.

    Kim, T., Kim, D.S.: Degenerate Laplace transform and degenerate gamma function. Russ. J. Math. Phys. 24(2), 241–248 (2017)

    MathSciNet  Article  Google Scholar 

  11. 11.

    Kim, T., Kim, D.S.: Degenerate polyexponential functions and degenerate Bell polynomials. J. Math. Anal. Appl. 487(2), 124017 (2020)

    MathSciNet  Article  Google Scholar 

  12. 12.

    Kim, T., Kim, D.S., Kim, H.-Y., Lee, H., Jang, L.-C.: Degenerate poly-Bernoulli polynomials arising from degenerate polylogarithm. Adv. Differ. Equ. 2020, Article ID 444 (2020)

    MathSciNet  Article  Google Scholar 

  13. 13.

    Kim, T., Yao, Y., Kim, D.S., Jang, G.-W.: Degenerate r-Stirling numbers and r-Bell polynomials. Russ. J. Math. Phys. 25(1), 44–58 (2018)

    MathSciNet  Article  Google Scholar 

  14. 14.

    Ma, Y., Kim, D. S., Kim, T., Lee, H.: Some identities of Lah–Bell polynomials. Adv. Differ. Equ. 2020, Article ID 510 (2020)

    MathSciNet  Article  Google Scholar 

  15. 15.

    Riordan, J.: Combinatorial Identities. Wiley, New York (1968)

    Google Scholar 

  16. 16.

    Simsek, Y.: Generating functions for generalized Stirling type numbers, array type polynomials, Eulerian type polynomials and their applications. Fixed Point Theory Appl. 2013, Article ID 87 (2013)

    MathSciNet  Article  Google Scholar 

Download references

Acknowledgements

Authors are thankful to the referees for their useful suggestions.

Availability of data and materials

Not applicable.

Funding

This research was supported by the Daegu University Research Grant, 2020.

Author information

Affiliations

Authors

Contributions

TK and DSK conceived of the framework and structured the whole paper; DSK and TK wrote the paper; HL and JWP checked the results of the paper and typed the paper; DSK and TK completed the revision of the article. All authors have read and agreed to the final version of the manuscript. All authors read and approved the final manuscript.

Corresponding author

Correspondence to Jin-Woo Park.

Ethics declarations

Competing interests

The authors declare no conflict of interest.

Rights and permissions

Open Access This article is licensed under a Creative Commons Attribution 4.0 International License, which permits use, sharing, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons licence, and indicate if changes were made. The images or other third party material in this article are included in the article’s Creative Commons licence, unless indicated otherwise in a credit line to the material. If material is not included in the article’s Creative Commons licence and your intended use is not permitted by statutory regulation or exceeds the permitted use, you will need to obtain permission directly from the copyright holder. To view a copy of this licence, visit http://creativecommons.org/licenses/by/4.0/.

Reprints and Permissions

About this article

Verify currency and authenticity via CrossMark

Cite this article

Kim, T., Kim, D.S., Lee, H. et al. A note on degenerate r-Stirling numbers. J Inequal Appl 2020, 225 (2020). https://doi.org/10.1186/s13660-020-02492-9

Download citation

Keywords

  • Unsigned degenerate r-Stirling numbers of the first kind
  • Degenerate r-Stirling numbers of first kind
  • Degenerate r-Stirling numbers of second kind